A Simple Computer Code for Result Analysis of University Graduates - Natarajan, N.; Vasudevan, M.; Venkatesh, A. (Journal of Engineering Education Transformations, 2025)
In the realm of higher education, efficient and user-friendly tools for result analysis play a pivotal role in evaluating the academic performance of university graduates. A systematic processing of the examination results and their meaningful representation requires enormous labor when attempted manually. The students are generally unaware of the computational metrics of semester grade point average (SGPA) and cumulative grade point average (CGPA) though they like to get updated on their performance periodically. In this study, a straightforward computer code is developed in C++ language to enable the students to calculate their academic progress (in terms of SGPA and CGPA) using the input data of marks and credits of individual subjects. The code is designed with simplicity and practicality in mind, to enable the students, parents, teachers and administrators with a versatile tool for comprehensively assessing the academic outcomes. The validity of the software program is verified by comparing the computational performance for three Indian universities, namely, Anna University, University of Madras and Indraprastha University in estimating the SGPA and CGPA on a 10-point scale. The results suggest that the code provides an accurate and time-saving solution compared to manual calculation. The results demonstrate the code's ability to verify the grades by the students as well as their mentors to keep track of the performance. This user-friendly tool will be highly beneficial for streamlining the result analysis process, providing valuable insights for the academicians towards decision-making and strategic planning.